Adaptation of Teaching-Learning Models Due to Covid-19 Pandemic: Challenge Towards Teachers Problem-Solving Skills - Munastiwi, Erni (Universitas Pendidikan Ganesha, 2021)
Pandemic covid-19 has a significant impact on the world of education. Changes in the learning system affect the learning process. The problem arises felt by educators of east Kalimantan palm oil plantations related to online learning support facilities. Network limitations and communication tools become a separateÂ¬Â¬ problem in educating the nation's children during the covid-19 pandemic. This study aims to identify strategies, methods, obstacles, and solutions for teachers in solving problems during the covid-19 pandemic. The research was conducted through qualitative methods, involving three elementary school teachers. Observation data retrieval techniques, interviews, and documentation. Test the data's validity by triangulation the sources .the research subjects of three educators in Teladan Prima Benua Baru and Teladan Prima 01 elementary schools. Data analysis using Miles &Huberman consists of three activities that coincide: data reduction, data presentation, conclusion drawing. The results showed obstacles, namely smartphone ownership, the unavailability of network coverage for the internet, TV, radio, limited teaching materials, student home distance, student discipline, parental limitations in accompanying children to learn, and time constraints. Teacher problem-solving strategies include implementing blended learning, creating learning groups, regular visits to students, partnering with parents, adapting teaching plans, optimizing electronic media, and utilizing creative media. Thus, aspects of problem-solving skills are essential for educators.